2022
DOI: 10.22271/j.ento.2022.v10.i4b.9018
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of neem bio-pesticide and synthetic insecticides against control of fall armyworm (Spodoptera frugiperda) in Maize

Abstract: Fall Armyworm (FAW), Spodoptera frugiperda, is prevalent in Zimbabwe, causing significant damage to maize and yield losses. Three synthetic insecticides (Nemesis, Ecoterex and Lamda-cyhalothrin) belonging to different chemical groups and neem bio-pesticide (Neem Leaf Extract) were tested for their efficacy against FAW under laboratory and field conditions. The aim of the study was to assess the effect of neem bio-pesticide and synthetic insecticides on the population of FAW larvae, level of leaf damage and mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 11 publications
7
7
0
Order By: Relevance
“…Lambda Cyhalothrin 5% EC (1.70), was found to be the next best treatment which is in line with the findings of Charitha and Kumar (2023) [9] , Patidar et al (2022) [24] , Khairul et al (2022) [20] . Thiamethoxam 12.6% + Lambda Cyhalothrin 9.5% ZC (1.84) was found to be the next best treatment which is in line with the findings of Sangle et al (2020) [25] , Kumari et al (2020) [21] . Thiamethoxam 25% WG (2.078) was found to be the next best treatment which is in line with the findings of Mallapur et al (2019) [22] , and Ingavale (2021).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Lambda Cyhalothrin 5% EC (1.70), was found to be the next best treatment which is in line with the findings of Charitha and Kumar (2023) [9] , Patidar et al (2022) [24] , Khairul et al (2022) [20] . Thiamethoxam 12.6% + Lambda Cyhalothrin 9.5% ZC (1.84) was found to be the next best treatment which is in line with the findings of Sangle et al (2020) [25] , Kumari et al (2020) [21] . Thiamethoxam 25% WG (2.078) was found to be the next best treatment which is in line with the findings of Mallapur et al (2019) [22] , and Ingavale (2021).…”
Section: Resultssupporting
confidence: 85%
“…The United States of America (USA) is the largest producer of maize contributing nearly 36% of the total production in the world (APEDA, 2015) [3] . India ranks sixth in global maize production and fifteenth position in its productivity in the world, contributing to 2.4 percent of world production with almost a 5 percent share in world harvested area (Sangle et al, 2020) [25] . The predominant maize-growing states that contribute more than 80 percent of the total maize production are Andhra Pradesh (20.9%), Karnataka (16.5%), Rajasthan (9.9%), Maharashtra (9.1%), Bihar (8.9%), Uttar Pradesh (6.1%), Madhya Pradesh (5.7%), Himachal Pradesh (4.4%).…”
Section: Introductionmentioning
confidence: 99%
“…There were significant differences observed among the treatments in terms of reducing FA larvae populations at various time intervals after treatment application (Kumar, 2021). This aligns with the study conducted by Bharadwaj et al (2020), which also reported significant reductions in the populations of FA larvae with the application of different insecticides.…”
Section: Discussionsupporting
confidence: 89%
“…The maize (Zea mays L.), a member of the Poaceae family, is an important cereal crop grown extensively in temperate, subtropical, and tropical regions of the world (Sangle et al, 2020). In Nepal, maize occupies a prominent position as the second most cultivated crop after rice in terms of both area and production, with an annual growth rate of 5% from the previous year.…”
Section: Introductionmentioning
confidence: 99%
“…The next best treatment was found to be Spinosad 45% SC in which the efficacy values of first and second spray were (2.86) and (1.46) respectively; these results were supported by Mallapur et al [20] and Sangle et al [21]. The next effective treatment was found to be Profenophos 50% EC in which efficacy values of first and second sprays were (2.93) and (1.53) respectively; these results were supported by Sangle et al [21]. The efficacy of Cypermethrin 10% EC on fall armyworm in first and second spray were (2.99) and (1.59).…”
Section: Overall Mean (First and Secondmentioning
confidence: 53%